Surgery for Bacterial Endocarditis Complicated by Diffuse Alveolar Hemorrhage - Kazuhiro Kurisu; Hiroshi Mitsuo; Yasutaka Ueno (Case Reports in Cardiology)
Diffuse alveolar hemorrhage is a very rare but potentially lethal condition resulting from various disorders. We report the case of a patient who suffered diffuse alveolar hemorrhage subsequent to bacterial endocarditis and survived aortic valve replacement, which was applied after improvement in respiratory distress. We believe that the strategy of respiratory functional recovery by aggressive rehabilitation is essential for the achievement of a successful surgical outcome in patients with alveolar hemorrhage.